Entre autos e vidas: um estudo de casos e processos criminais de feminicídio na Comarca de Fortaleza entre 2015 e 2019 e os limites do sistema protetivo à violência letal de gênero - Araújo, Geórgia Oliveira (2021)
The research deals with the characterization of the subjects involved as victims and accused in cases of lethal gender violence and the limits of the legal-protective apparatus established by the justice system for women in situations of violence in cases of femicide that occurred in the city of Fortaleza between March 2015 and December 2019. It uses the framework of intersectional feminist theories and critical and feminist criminology to analyze the emergence of the concept of femicide, as well as its translation as a criminal rule to meet the demands of feminist movements. It discusses the normative system established by the Maria da Penha Law and its repercussions on the Brazilian legal system. It examines the limitations of existing statistics on femicide in Brazil and Ceará and the difficulties in accessing data on gender violence from agencies linked to public security and the Judiciary. It adopts a methodology of document analysis and quantitative and qualitative data collection from 58 criminal cases of femicide to characterize the victims and the accused of these crimes, examine the degree of relationship between them, collect information about the crime and the flow of justice in the criminal lawsuit and question the role of the Maria da Penha Law's protective system in cases of femicide. As limitations, it faces the absence of a public and reliable database of the number of cases of femicide in the state of Ceará and, more specifically, in the city of Fortaleza. It concludes for the greater vulnerability of black women aged between 19 and 39 years, with low education and living on the outskirts of Fortaleza, who are killed in the domestic environment and in a context of intimate relationships by partners and ex-partners, who are also black and cater to the same age group. It points out as a gap in the analyzed data the absence of feminicides of transgender women. It also concludes for the underutilization of protective mechanisms such as urgent protective measures in the context of the studied feminicides. It starts from the perception of femicide as part of a circuit of violence that intertwines with other social markers of difference to conclude for the need to develop specific policies aimed at preventing and dealing with lethal gender violence, providing assistance to surviving victims and to family members affected by the crime.